(untitled) - Witte, Raymond H. (New York, 2012)
Classroom Assessment for Teachers provides students with essential professional knowledge/skill sets along with contemporary issues surrounding the assessment of student learning progress and achievement. By utilizing an inquiry-oriented approach, pre-service teacher candidates can explore the essential relationship between assessment and teaching with a deliberate focus on encouraging students to construct their own assessment framework and select measures and procedures that are designed to meet their own needs along with those of their students.
Đánh giá kết quả học tập Toán và Khoa học tự nhiên
Keywords: Trách nhiệm giáo dục,Educational accountability,Academy achievement,Thành tích Học viện; Hoa Kỳ,United States,United States,Hoa Kỳ